2016
DOI: 10.1097/ccm.0000000000001352
|View full text |Cite
|
Sign up to set email alerts
|

Successful Extracorporeal Life Support in a Case of Severe Glyphosate-Surfactant Intoxication

Abstract: On the basis of our research, this was the first case in which extracorporeal membrane oxygenation was used to treat severe glyphosate-surfactant intoxication. We recommend early initiation of extracorporeal membrane oxygenation therapy to mitigate cardiopulmonary compromise in patients with glyphosate-surfactant intoxication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The successful use of ECMO in the treatment of adult poisoned and trauma patients has been previously described in case reports and small case series. 2,3,514,16,19 In our case series we successfully employed ECMO in five patients following suspected or confirmed suicide attempts. All five patients were discharged from the hospital, but some had prolonged courses with complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful use of ECMO in the treatment of adult poisoned and trauma patients has been previously described in case reports and small case series. 2,3,514,16,19 In our case series we successfully employed ECMO in five patients following suspected or confirmed suicide attempts. All five patients were discharged from the hospital, but some had prolonged courses with complications.…”
Section: Discussionmentioning
confidence: 99%
“…ECMO has been used successfully to support patients following suicide attempts. 2,3 Both veno-arterial (VA) and veno-venous (VV) ECMO have been employed for cardiotoxic ingestions 513 and poisoning complicated by respiratory failure 14 , respectively, and in trauma patients without suicide attempts who develop acute respiratory distress syndrome (ARDS) or thoracic organ contusion. 1518 A retrospective cohort analysis of 62 patients following drug intoxication (intentional and unintentional) compared the use of ECMO in 14 patients to conventional medical therapy in 48 patients and suggested a survival benefit in the ECMO group.…”
Section: Introductionmentioning
confidence: 99%
“…With the removal of the organophosphorus pesticides, cardiac function can be restored by the application of ECMO. Therefore, we recommend that for patients with refractory cardiogenic shock caused by AOPP, ECMO should be implemented early after the failure of conventional therapy [18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…However, we still lack experience regarding the role of ECMO in the treatment of diquat and glyphosate poisoning, with few case reports. [12,15,16] It has been reported that ECMO was effective for patients with glyphosate poisoning complicated with cardiovascular and respiratory damage.…”
Section: Discussionmentioning
confidence: 99%